EFFECTIVENESS OF URBAN FARMING POLICIES AND ECONOMIC HEROES IN POVERTY REDUCTION IN THE CITY OF SURABAYA - Arimurti Kriswibowo; Khusnul Khothimah; Rhea Ardhana (NATAPRAJA, 2020)
Poverty in Indonesia raises various complex problems such as unemployment, crime, and other social problems. Surabaya is one of metropolitan city in Indonesia, yet still has a high poverty rates. Various attempts have been made by the Surabaya City Government to overcome the problem of poverty. Some of the policies implemented by the Surabaya City Government are Urban Farming Program and UMKM Tangible Economy Heroes Program. This study wants to answer empirically how effective the program is. Effectiveness according to Budiani (2007: 53) can be measured through the determination of program objectives, program socialization, program objectives, and program monitoring. This program takes place in Kelurahan Keputih and Rungkut Lor, Surabaya using a comparative descriptive method with a qualitative approach. The Urban Farming Program is a program to spur improvement in the living standards of the poor who are engaged in strengthening the urban agriculture sector. The Urban Farming Program is felt to be lacking in accuracy of the program targets due to incompatible products produced with demand, incompatible characteristics of the area with what is planted, and products produced can only be consumed alone. Intangible UMKM Economic Heroes Program is a program to empower housewives from poor families and MSME entrepreneurs. The Intangible Economy Hero Program of UMKM is deemed effective in minimizing poverty.